RANCANG BANGUN ALAT MINI GAS ANALYZER KENDARAAN BERMOTOR MENGGUNAKAN SENSOR MQ7, MQ6 DAN MIKROKONTROLLER ARDUINO UNO - huri, mas; Agustian Yulanda , Erik (Jurnal Qua Teknika, 2025)
Abstract: Motor vehicle exhaust is a major contributor to air pollution and can have a negative impact on health and the environment, so it is important to have a vehicle exhaust gas measurement tool, to ensure that vehicle exhaust is at the tolerance level set by the government. This study aims to create a mini gas analyzer tool based on Arduino Uno that can measure carbon monoxide (CO) and hydrocarbon (HC) levels in motor vehicle exhaust. The tool design uses an MQ7 sensor to measure CO and an MQ6 sensor to measure HC and Arduino Uno as a data processor. Tool testing was carried out by experimenting with several vehicles with different engine conditions. The test results showed an average error of 1.89% for CO and 0.375% for HC when compared to conventional tools. The test results show the potential of the tool for use in mass emission testing programs Keywords: Gas analyzer; Carbon Monoxide; Hydrocarbon; MQ7 Sensor; MQ6 Sensor; Emission Testing.